Neutrophilic pustular eruption with behcet's like illness post Covid-19 vaccination - Anmol Bhargava; Vidya Kharkar; Sunanda Mahajan; Prachi Gole (Wolters Kluwer Medknow Publications, 2022)
The COVID-19 pandemic has deeply impacted the lives of many. In such unprecedent times, mass vaccination has been the cornerstone in decreasing morbidity and mortality. However, various adverse events (AEs) to COVID-19 vaccines including cutaneous AEs have been reported worldwide. We report a case of neutrophilic pustular eruption with a Behcet's disease-like illness following COVID-19 vaccination with no history of known allergies or prior severe acute respiratory syndrome Coronavirus 2 (SARS-CoV-2) infection.